Escherichia coli vacuolating factor, involved in avian cellulitis, induces actin contraction and binds to cytoskeleton proteins in fibroblasts - Aragão,Annelize Zambon Barbosa (2021)
Abstract Background Avian pathogenic Escherichia coli (APEC) isolated from avian cellulitis lesions produces a toxin, named Escherichia coli vacuolating factor (ECVF), that causes cell vacuolization and induces inflammatory response in broiler chicken. Methods We investigated the intracellular activities of ECVF in avian fibroblasts using fluorescence staining, electron microscopy, MTT and LDH measurements. As ECVF act specifically in avian cells, we performed blotting assay followed by mass spectrometry to better understand its initial intracellular protein recognition. Results ECVF induced actin contraction, mitochondrial damage and membrane permeability alterations. Ultrastructural analysis showed intracellular alterations, as nuclear lobulation and the presence of degraded structures inside the vacuoles. Moreover, ECVF induced cell death in fibroblasts. ECVF-biotin associates to at least two proteins only in avian cell lysates: alpha-actinin 4 and vinculin, both involved in cytoskeleton structure. Conclusion These findings demonstrated that ECVF plays an important role in avian cellulitis, markedly in initial steps of infection. Taken together, the results place this toxin as a target for drug and/or vaccine development, instead of the use of large amounts antibiotics.